2006
DOI: 10.5070/v422110064
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Human Health Hazards from Broadcast Application of 0.005% Diphacinone Rodenticide Baits in Native Hawaiian Ecosystems

Abstract: In the early 1990s, a coalition of federal and state agencies, NGOs, and private landowners in Hawaii agreed to pursue a Special Local Needs pesticide registration [24(c) FIFRA] for the aerial broadcast of a 0.005% diphacinone rodenticide for the control of rodents in native ecosystems. While there was recognition of the important role introduced rodents play in the decline and extinction of native species, there were concerns expressed about the potential non-target impacts of this technique. Over the next 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
(42 reference statements)
2
24
0
Order By: Relevance
“…In an often cited trial by Savarie et al (1979), seven captive golden eagles (Aquila chrysaetos) were fed muscle for 5 or 10 days from sheep (Ovis aries) that had been dosed with DPN (30 mg/kg), and then the eagles were switched to untreated food for 11 days. Prothrombin time more than doubled at doses as low as 0.11 mg/kg/day (cumulative dose as low as 0.55 mg/kg) (Eisemann and Swift 2006). Two of the eagles (daily doses: 0.22 and 0.14 mg/ kg/day; cumulative doses: 1.08 and 1.38 mg/kg) exhibited muscular weakness and extreme ataxia, and one of these bled from wounds on the wings and feet.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In an often cited trial by Savarie et al (1979), seven captive golden eagles (Aquila chrysaetos) were fed muscle for 5 or 10 days from sheep (Ovis aries) that had been dosed with DPN (30 mg/kg), and then the eagles were switched to untreated food for 11 days. Prothrombin time more than doubled at doses as low as 0.11 mg/kg/day (cumulative dose as low as 0.55 mg/kg) (Eisemann and Swift 2006). Two of the eagles (daily doses: 0.22 and 0.14 mg/ kg/day; cumulative doses: 1.08 and 1.38 mg/kg) exhibited muscular weakness and extreme ataxia, and one of these bled from wounds on the wings and feet.…”
Section: Discussionmentioning
confidence: 98%
“…A considerable effort has been expended on assessing the hazard of DPN to non-target wildlife as part of an application for a Special Local Needs pesticide registration for its broadcast application for control of rodents and other pests in Hawaii (Johnston et al 2005;Eisemann and Swift 2006). These assessments concluded that the risk associated with acute exposure to DPN would be minimal for several endangered species (e.g., black-faced honeycreeper, Melamprosops phaeosoma, Hawaiian short-eared owl, and Hawaiian hawk), although the Hawaiian crow (Corvus hawaiiensis) was identified as possibly being at risk of lethal effects from direct ingestion of bait (primary exposure).…”
Section: Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This toxicity database represents data that were used by USEPA in pesticide ecological risk assessments. This is common practice in ecological risk assessment when the only data available is survival at the highest dose (e.g., [27] for birds and rodenticides). We used a correlation analysis to determine if there was a significant relationship between the limited reptile and bird data that is currently available.…”
Section: Relationship Between Reptile and Bird Ld50smentioning
confidence: 99%
“…or their parts are used by local fisherman as bait on their hooks. Tanner et al (2004) found diphacinone residue in coconut crab tissues after feeding bait and diphacinone-poisoned rats to coconut crabs, and although no recommendation for safe levels of consumption were given, Eisemann and Swift (2006) indicated that the residues in crab tissues were much lower than the residues used for risk measurements. Thus, risk from eating crabs was negligible.…”
Section: Mitigating Non-target Concernsmentioning
confidence: 99%